PENGEMBANGAN PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS KONTEKS ISLAM UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA PADA MATERI MATRIKS KELAS XI - Agus Maqruf (IAIN Purwokerto, 2020)
Understanding is a first skills that must be mastered by students. In learning mathematics, understanding skills are important for students to have good learning outcomes. Because of the importance of these abilities, treatment is needed to improve students' understanding of mathematics in the process of learning mathematics. One of the supporting factors of learning is teaching material. Good teaching materials will be able to support learning as well. Conventional teaching materials have certainly been widely applied in schools or madrassas. Through these teaching materials, researchers used one of the treatments that could be done, namely the development of Student Contexts Based on Islamic Contexts. This study aims to development of valid and effectiveâ€™s student worksheet to increase studentâ€™s mathematics understanding in matrix materials for class XI. The research method used in this thesis is Research and Development with quasi experiment. The results of this study indicate that the Islamic Contextual Based Worksheet is valid and interesting as the results of the validation of material experts with a score of 3.49 â€œvalidâ€ category, teaching material experts with a score of 2.97 â€œquite validâ€ category, validation of Islamic context experts with a score of 3.38 â€œvalidâ€ category, teacher ratings with a score of 2.95 â€œinterestingâ€ category, assessment of small group test students with a score of 3.34 â€œ very interestingâ€ category and assessment of field test students with a score of 3.10 â€œinterestingâ€ category. Furthermore, the results of Islamic Contextual Based Worksheet are also effective to improve students' mathematical understanding in class XI MAN 2 Banyumas with the experimental class N-Gain score of 0.411 with medium category, which is better than the control class N-Gain score of 0.073 with low category.